Impact of Entrepreneurship on Economic Growth of Farmers in Manipur - Singh, N. Muhindro; Savino, N.; Singh, M. Dhaneswar; Kumar, Hemant; Devi, A. Ameeta (Indian Journal of Extension Education, 2016)
The present study was carried out on 400 households, belonging to 4 blocks of Senapati district of Manipur during 2013- 15. Senapati district was selected keeping in view of major concentration of tribals with highest pig population in the state  of Manipur. A sample of farmers comprising of 100 respondents from each block was selected for the present study.  Locations had significant (P
Keywords: Economic Growth; Entrepreneurship and Pigs